Сердце из льда: [повесть] / Мария Северская - Северская Мария (Только для девчонок, 2014)
Экземпляры: ОРФ (20140910) / Инвентарный номер: 50892 / Цена: 172. 00. / Сис.шифр: Р2 / Авт.знак: С 28 / ББК: 84(2Рос-Рус)6-4